Prognostic nomograms for gastric carcinoma after surgery to assist decision-making for postoperative treatment with chemotherapy cycles <9 or chemotherapy cycles ≥9 - Li, Yifan; Zhang, Xiaojuan (Frontiers in Surgery, 2022)
Objective: We sought to develop novel nomograms to accurately predict overall survival (OS) of chemotherapy cycles<9 and chemotherapy cycles≥9 and construct risk stratification to differentiate low-risk and high-risk of two cohorts . Methods: Patients who underwent curative-intent resection for gastric cancer between January 2002 and May 2020 at a single China institution were identified. Variables associated with OS were recorded and analyzed according to multivariable Cox models. Nomograms predicting 3- and 5-year OS were built according to variables resulting from multivariable Cox models. Discrimination ability was calculated using the Harrell’s Concordance Index. The constructed nomogram was subjected to 1,000 resamples bootstrap for internal validation. Calibration curves for the new nomograms were used to test the consistency between the predicted and actual 3- and 5-year OS. Decision curve analysis (DCA) was performed to assess the clinical net benefit. The Concordance index (C-index) and time-dependent receiver operating characteristic (t-ROC) curves were used to evaluate and compare the discriminative abilities of the new nomograms. Finally, prognostic risk stratification of gastric cancer was conducted with X-tile software and nomograms converted into a risk-stratified prognosis model. Results: For the nomogram predict OS of chemotherapy cycles <9, C-index was 0.711 (95%CI: 0.663-0.760) in internal validation and 0.722(95%CI:0.662-0.783) in external validation, which was better than AJCC 8th edition TNM staging (internal validation:0.627 ,95%CI: 0.585-0.670) and (external validation:0.595,95%CI:0.543-0.648). The C-index of the nomogram for chemotherapy cycles≥9 in internal validation was 0.755 (95%CI: 0.728-0.782) and 0.785(95%CI:0.747-0.823) in external validation, which was superior to the AJCC 8th edition TNM staging (internal validation: 0.712 95%CI: 0.688-0.737) and (external validation 0.734, 95%CI:0.699-0.770). Calibration curves, t-ROC curves and DCA of the two nomogram models showed that the recognition performance of the two nomogram models was outstanding. The statistical differences in the prognosis among the two risk stratification groups further showed that our model had an excellent risk stratification performance. Conclusion: This is first reported risk stratification and nomogram for chemotherapy cycles of gastric carcinoma. Nomograms for predicting OS shows a good distinction between internal validation and external validation cohorts, the risk stratification systems will provide accurate guidance of postoperative treatment of gastric carcinoma